The Discovery of New Deep-Sea Hydrothermal Vent Communities in the Southern Ocean and Implications for Biogeography - Rogers, Alex D.; Tyler, Paul A.; Connelly, Douglas P.; Copley, Jon T.; James, Rachael; Larter, Robert D.; Linse, Katrin; Mills, Rachel A.; Garabato, Alfredo Naveira; Pancost, Richard D.; Pearce, David A.; Polunin, Nicholas V. C.; et al. (PLOS Biology, 2012)
A survey of Antarctic waters along the East Scotia Ridge in the Southern Ocean reveals a new vent biogeographic province among previously uncharacterized deep-sea hydrothermal vent communities.